Sociocultural neotraditionalism: rehabilitation of traditions and reproduction of ethnicity - Popkov, Yuri V.; Madiukova, Svetlana A. (The New Research of Tuva, 2010)
Article represents the text of lecture at the round table “Sociocultural neotraditionalism and steady development of Russian regions” of the conference “Regions for steady development: education and culture of the people of Russian Federation” (March 25-27, 2010, Novosibirsk).